Analysis Of Climate Variability On Drought Index In Sleman District - Rayi Putri Anggraeni; Jasruddin Jasruddin; Agus Susanto (International Journal Labs, 2024)
Climate change occurs due to global warming, resulting in irregular seasonal shifts and ecological disasters such as floods or droughts that cause substantial losses. This research aims to determine the influence of climate variability on drought conditions by analyzing drought using the Standardized Precipitation Index (SPI) method. The data used consists of monthly rainfall over 40 years, from 1981 to 2020, obtained from CHIRPS satellite and observation data located in Sleman District. From the 40-year data divided into ten-year periods, severe droughts occurred in the second and fourth periods, specifically from 1991 to 2000 and from 2011 to 2020. The highest frequency of drought occurrences from the entire dataset also happened during the 1991-2000 period. Climate variability, based on the Schmidt-Ferguson climate types, shows climate changes by calculating the Q value. Initially, from 1981 to 1990, the Q value ranged from 33.3 to 60, categorized under type C climate. However, from 1991 to 2000, the Q value ranged from 33.3 to 100, with climate types categorized as C and D. Climate pattern changes have occurred from 2001 to 2010, with climate types ranging from B to D. Spatial analysis scale changes were observed from 2011 to 2020. These conditions indicate climate pattern changes in Sleman District over the 40-year period. The relationship between drought index and SPI method with climate variability (Q) values indicates a weak to moderate relationship with a significance level of 5%. This suggests climate change affects rainfall patterns and drought levels. The correlation coefficient values indicate a moderate relationship, with correlation coefficient values ranging from 0.3 to 0.5 highest during period II (1991-2000) and period IV (2011-2020).